Long-term survival following initiation of home non-invasive ventilation: a European study. Issue 11 (7th September 2020) - Patout, Maxime; Lhuillier, Elodie; Kaltsakas, Georgios; Benattia, Amira; Dupuis, Johan; Arbane, Gill; Declercq, Pierre-Louis; Ramsay, Michelle; Marino, Philip; Molano, Luis-Carlos; Artaud-Macari, Elise; Viacroze, Catherine; et al.
Abstract : Introduction: Although home non-invasive ventilation (NIV) is increasingly used to manage patients with chronic ventilatory failure, there are limited data on the long-term outcome of these patients. Our aim was to report on home NIV populations and the long-term outcome from two European centres. Methods: Cohort analysis including all patients established on home NIV from two European centres between 2008 and 2014. Results: Home NIV was initiated in 1746 patients to treat chronic ventilatory failure caused by (1) obesity hypoventilation syndrome±obstructive sleep apnoea (OHS±OSA) (29.5%); (2) neuromuscular disease (NMD) (22.7%); and (3) obstructive airway diseases (OAD) (19.1%). Overall cohort median survival following NIV initiation was 6.6 years. Median survival varied by underlying aetiology of respiratory failure: rapidly progressive NMD 1.1 years, OAD 2.7 years, OHS±OSA >7 years and slowly progressive NMD >7 years. Multivariate analysis demonstrated higher mortality in patients with rapidly progressive NMD (HR 4.78, 95% CI 3.38 to 6.75), COPD (HR 2.25, 95% CI 1.64 to 3.10), age >60 years at initiation of home NIV (HR 2.41, 95% CI 1.92 to 3.02) and NIV initiation following an acute admission (HR 1.38, 95% CI 1.13 to 1.68). Factors associated with lower mortality were NIV adherence >4 hours per day (HR 0.64, 95% CI 0.51 to 0.79), OSA (HR 0.51, 95% CI 0.31 to 0.84) and female gender (HR 0.79, 95% CI 0.65 to 0.96). Conclusion: The mortality rate following initiation of home NIV is high but varies significantly according to underlying aetiology of respiratory failure. In patients with chronic respiratory failure, initiation of home NIV following an acute admission and low levels of NIV adherence are poor prognostic features and may be amenable to intervention.